Social Media Strategy: The Use of Social Media in Stationery Business to Reach Gen Z - Suhartono, Natasya Priscilla (VCD, 2022)
In the creative industry world, many start-up stationery businesses have started to emerge which still have an audience base. The main target market is Gen Z teenagers who are actively using social media. To be able to reach Gen Z, the right marketing strategy is needed to create brand awareness of the stationary business. Therefore, it is necessary to study literature on social media strategies, brand communication and Gen Z behavior in using social media. From the results of the literature study, it can be said that social media content that is simple, relevant, and repeatable is effective in building relationships between stationery and consumers on social media. It is hoped that with optimal use of social media, brand awareness of the stationary business will also increase. Keywords: Social Media Strategy, Gen Z, Brand Communication